Strengthening mechanisms in high-entropy alloys: Perspectives for alloy design. Issue 19 (14th October 2018) - Rivera-Díaz-del-Castillo, Pedro E.J.; Fu, Hanwei
Abstract: Abstract : High-entropy alloys (HEAs), originally introduced to the literature due to their ability to stabilize a single phase across large temperature ranges, have recently demonstrated to display multiphase systems undergoing a variety of strengthening mechanisms. Previous reports have focused on solid solution strengthening and precipitation hardening; however, other hardening mechanisms such as twinning and martensite formation have been reported to play a key role in controlling their mechanical behavior. Such deformation mechanisms display significant variations with temperature and strain rate. The present contribution provides an outline of the various hardening mechanisms reported in the literature for HEAs. For each mechanism, a modeling strategy is proposed to describe the associated mechanical behavior. The mechanisms are combined into a single framework to discover new HEAs of improved mechanical behavior. A strategy for HEA design is presented, and the advantages of adopting additive layer manufacturing to improve mechanical behavior are discussed.